Experimental studies on air entrainment and oxygen content downstream of sharp-crested weirs - Baylar, Ahmet; Bagatur, Tamer (Blackwell Publishing, 2006)
The concentration of dissolved oxygen (DO) is an important indicator of water quality because aquatic life survives on the DO in water. A free overfall jet from a weir plunging into downstream water causes entrainment of air bubbles if the free overfall jet velocity exceeds a certain critical value and hence aeration occurs. This paper investigates the free overfall jets from sharp-crested weirs and their effect on air entrainment and aeration efficiency. The results indicate that the air entrainment and aeration efficiency of triangular sharp-crested weirs are significantly better than those for the other sharp-crested weir types. Therefore, the triangular sharp-crested weirs can be used as highly effective aerators in streams, rivers, constructed channels, fish hatcheries, water treatment plants, etc. Regression equations were obtained for the triangular sharp-crested weirs relating air entrainment rate and aeration efficiency to drop, height, discharge and angle in the triangular sharp-crested weir. There was good agreement between the measured values and the values computed from the predictive equations.
Keywords: aeration efficiency; air entrainment rate; dissolved oxygen; weir